Morphological criteria of animals' organism adaptation in combined effect of electromagnetic radiation and positive low temperature (Environment & Health, 2016)
Objective. We established the nature of morphological and functional changes in the internal organs of the laboratory animals in isolated effect of electromagnetic radiation (EMR) and joint effect of EMR with a positive low temperature in the experiment as well.Materials and methods. The study was carried out in a subacute laboratory experiment (30 days) in white male rats. At the end of the experiment, the following internal organs were isolated: liver, kidneys, adrenals, testes, thyroid, and spleen. Histological studies were performed using conventional histological techniques and methods of histochemistry.Results. The morphological changes in internal organs of the animals exposed to EMR were characterized by the state of the functional tension that was the body's response to the effect of impact of hazardous factors.However, the influence of EMR at the joint effect with cold factor was more pronounced on the part of the endocrine system, it confirms a decrease of the resistance of the experimental animals’ organism in this group.Conclusion. The isolated action of EMR led to the development of adaptive reactions of the organism. At the same time, the effect of EMR in conditions of cold stress for 30 days resulted in disruption of adaptation mechanisms and contributed to occurrence of pathological changes.
Keywords: cold factor; electromagnetic radiation; morphological changes; adaptation; animal organism